One-Year Outcomes of Modified Technique for Scleral Fixation of a Three-Piece Intraocular Lens Without Conjunctival Opening - Ye, Hongfei; Zhang, Shiguang; Mi, Wei; Fei, Ping; Zhao, Peiquan (Frontiers in Medicine, 2022)
Purpose: To present the one-year follow-up of a modified technique for scleral fixation of three-piece intraocular lens (IOL) without conjunctival incision. Methods: A retrospective chart review of a consecutive series of 10 eyes of 9 patients who underwent scleral IOL fixation using the modified technique was performed. Data were collected 1 year after surgery for all patients. Results: The range of follow-up time was between 1 year to 31 months. At the last follow-up point, the IOL was well-positioned and the visual acuity was good (as limited by primary disease). Short-term complications included pupillary IOL capture (n=1) and decreased intraocular pressure (n=1), no long-term complications were observed. Conclusion: Outcomes data support this technique as a viable option for management of secondary IOL fixation with flexible usage of more designs of IOLs.